Implementation of Warm Compress to Treat Back Pain in Pregnant Women in The Thirty Trimester - Ilham Juliyana; Elis Roslianti; Nur Hidayat (LPPM STIKes Muhammadiyah Ciamis, 2025)
Introduction: Pregnant women in the third trimester often experience back pain due to physiological changes, increased body weight, and a shift in the center of gravity. This discomfort can interfere with daily activities and maternal well-being. Pain management can be addressed through both pharmacological and non-pharmacological approaches. Warm compresses are a simple, safe, and effective non-pharmacological method to relieve pain during pregnancy. Objective: This study aimed to determine the effect of warm compress application on back pain intensity in a third-trimester pregnant woman. Method: This study used a descriptive case study design with a nursing care process approach. The subject in this study was one third-trimester pregnant woman who experienced back pain. The intervention given was in the form of giving warm compresses to the lower back twice a day for four consecutive days. Measurement of pain intensity was carried out using the Numeric Rating Scale (NRS) before and after the intervention. Data collection was carried out through interviews, observations, physical examinations, and documentation of the development of client nursing care systematically according to the stages of the nursing process. Results: After four days of intervention, the patient's back pain intensity decreased from a score of 6 (moderate pain) to 2 (mild pain). The patient reported improved comfort, reduced physical limitations, and no adverse effects from the intervention. Conclusion: Warm compress therapy is proven to be effective in reducing back pain intensity in third-trimester pregnant women. It can be recommended as an alternative non-pharmacological pain management strategy in maternity nursing care practices.